2006
DOI: 10.1007/s10464-006-9079-7
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Theory of Change Approach to Interagency Planning in Child Mental Health

Abstract: This paper describes the use of a theory of change approach to community-based cross-agency service planning for children with serious emotional disturbance and their families. Public agency planners in Contra Costa County, California used the theory of change approach to organize service planning for a population of youth who had been arrested and involved with juvenile probation. The theory of change process described in this paper links community outcomes with planned activities with the assumptions or prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…In their program, a community youth committee was involved in the development of the logic model and provided input into the content and delivery format of the intervention resulting in a more relevant, feasible and sustainable intervention. Similarly, Hernandez and Hodges [42] used ToC developed with stakeholders to organize services for youth in contact with the juvenile justice system. They found that ToC assisted with creating a shared vision among stakeholders which promoted service integration across a variety of sectors.…”
Section: Discussionmentioning
confidence: 99%
“…In their program, a community youth committee was involved in the development of the logic model and provided input into the content and delivery format of the intervention resulting in a more relevant, feasible and sustainable intervention. Similarly, Hernandez and Hodges [42] used ToC developed with stakeholders to organize services for youth in contact with the juvenile justice system. They found that ToC assisted with creating a shared vision among stakeholders which promoted service integration across a variety of sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Kellogg Foundation, 2004;Hernandez & Hodges, 2006). This type of logic model illustrates why a specific idea for a given programme is pursued.…”
Section: Theoretical Underpinning Of the Frameworkmentioning
confidence: 99%
“…Emphasis is placed on the 'bigger picture' or the whole. This allows reflection on the function of a system's parts based on their relationships with one another and within the system's larger context (Hernandez & Hodges, 2006;Frechtling, 2007). The larger context in this study refers to the healthcare system in which biomedical services are rendered to children exposed to or infected by HIV.…”
Section: Theoretical Underpinning Of the Frameworkmentioning
confidence: 99%
“…Key informant interviews (Walker et al 2003), review of wraparound training manuals and other program materials (Walker and Bruns 2006b), and observations of wraparound teams (Walker and Schutte 2005) yielded initial information regarding outcomes being sought, and how activities might be causally connected to outcomes. Again, as is often the case in post hoc program theory development (Donaldson 2007;Hernandez and Hodges 2006;Savaya and Waysman 2005), different individuals and different sources offered different ideas about why wraparound caused positive impacts and, for the most part, the actual rationales for these causal connections between activities and outcomes were described rather vaguely. Nevertheless, combining the information across these sources yielded good information about the intermediate-and longerterm outcomes that were typically assumed to result from wraparound, as well as a diverse set of ideas about how and why wraparound activities might contribute to the outcomes.…”
Section: A Theory Of Change For Wraparoundmentioning
confidence: 99%